Analysis and an overview of fixators in medicine and the methods of processing materials for producing fixators - Đenadić, Dalibor Milojko; Manić, Miodrag T.; Tanikić, Dejan I.; Ranđelović, Saša S.; Đekić, Petar S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The fixator is a medical device that provides support to fractured biological structures. Metal biomaterials are mainly used for replacing broken or damaged hard tissues such as bones because of their high strenght, toughness and corrosion resistance. Materials such as stainless steel, titanium and aluminium alloys (Ti-6Al-4V), cobalt and chromium alloys, composite materials and other biocompatible materials are used in orthopedy for the stabilization of connective tissue injuries or as a substitute for the bone tissues. Fixators are classified according to the place of installation to external and internal fixators. Widely used medical fixators are pins, rods plates, screws, pipes, wires, nails and external fixators. Conventional and non-conventional methods of processing are used in the production process for all types of fixators. Introduction Fixators are medical devices manufactured to support damaged biological structures. In the field of orthopedic surgery that deals with skeletal disorders such as bone, spine, joints, muscles and tendons injuries and diseases, various metals, titanium and cobalt alloys etc. are used to stabilize the supporting tissue injuries or as a substitute for bone tissues. Metallic implants are frequently used in orthopedic surgery as joint prosthesis (hip, knee and elbow) fracture fixation devices (plates, screws, external fixators) and devices for the fixation of the spine. In principle, fixators are devided into external and internal ones, depending on the place of installation (outside or inside the body). The most common types of medical fixators are pins, rods and plates. This paper presents some of the most common materials used for the production of fixators, their processing and possibilties of use in medicine for various purposes. Types of fixators and materials used for their production Nowadays, biocompatible materials are usually used for the production of fixators and implants. These materials show good performances in contact with cells, tissues or body fluids. They are commonly used to replace or upgrade the structural components of the human body in order to compensate for damage that occures due to aging, illness or accidents. These materials should have the following features: non-toxicity, resistance to corrosion, durability, high strength, toughness at low values of elastic modulus. The most commonly used materials in orthopedic surgery are stainless steels (with austenitic and precipitation strengthening), cobalt-based super-alloys (e.g. cobalt-chromium alloys), titanium and its alloys and sometimes composite materials. However, titanium and its alloys are primarly used. The implants for joint prosthesis are the tubes that are inserted into the medullary canal of the bone in order to stabilize prosthesis and parts of the joint. In total hip prosthesis, the femoral prosthesis head is usually made ​​of cobalt-chromium alloys, while the component that replaces the femur is made of titanium alloys. Fracture fixators include plates, screws, wire, nails and external fixators. They are made of different metal alloys, mostly of titanium alloys. Methods of manufacturing and processing materials used for fixators in medicine The main characteristics of the research in the field of materials used for fixators are: 1) New analytical techniques and modern instruments for characterization of materials (e.g. tunnel scanning microscope and synchrotron) 2) Computer simulations 3) Recognition capabilities, visual representation and quantification of structural forms in the micro and nano world using computer modeling 4) The material is immediately formed in the approximatelly final form of the workpiece ("Net shape" and "near net shape" procedures) 5) Production of new materials is closely associated with the procedures that are usually called "Materials Technologies" Materials and parts obtained using the powder metallurgy Modern materials are obtained by optimizing the composition and microstructure of the material to the desired properties Classical procedures PM Nowadays, these methods achieve equal or even better properties than those obtained by traditional methods of metal forming. Methods of powder forming today are also used in the manufacture of ceramics and metal composites. Modern methods of the manufacturing in the nearly final shape ("net shape and near net shape technologies") They can be classified into three categories: 1) Consolidation methods used to achieve full density 2) Plasma spraying and Spray forming 3) Rapid Prototyping and rapid production of parts (Rapid Manufacturing) One of the most interesting processes to produce parts in one operation is the laser deposition process (sintering) of metal powders, layer by layer. The best known method of forming in semi-solid state is thixomoulding. A water jet cutting is one of the most innovative methods nowadays. The Water Jet is the process of cold processing using a jet of water, which allows to work with materials that previously could not be processed using traditional methods (or only with great difficulties). Development of new alloys for future use Titanium alloys, especially alloys α + β type such as Ti-6Al-4V are considered the most suitable biocompatible metallic materials due to their excellent combination of mechanical properties, corrosion resistance and biocompatibility. The basic idea in the development of new alloys for use in medicine is to replace aluminum and vanadium with niobium, tantalum and zirconium, in order to avoid the negative features of widely used Ti-6Al-4V alloy. It is shown that the toxicity of these elements is extremely low. Some newly developed alloys are: Ti-3Al-2, 5V (α + β) Ti-5AL-2, 5Fe (α + β) Ti-6Al-7NB (α + β) Ti-15Mo (β) ; Ti-13Nb-13Zr (β) Ti-12mo-6Zr-2Fe (β) Ti-45Nb (β) Ti-35Nb-7Zr-5ta (β) Ti-55, 8Ni (intermetallic). The alloy that shows excellent properties is Ti-13Nb-13Zr. This alloy is a β-type titanium alloy. It is characterized by low values ​​of elastic modulus and significantly improved strenhth compared to the Ti-6Al-4V alloy, making it very attractive for applications in biomedical engineering. Conclusion Titanium and its alloys show significant advantages compared to other groups of biocompatible metallic materials used un medicine. Most of the materials studied in this article are not produced in Serbia, except for the stainless steel and certain alloys that can be produced in the Vinca Institut and the Sartid Smederevo company. However, there are a number of plants for processing of the studied materials, such Slovas from Cacak, Aquarez from Sremska Kamenica, etc. For example, Aquarez has CNC drives, as well as Water Jets. Similar plants can be found all around the former Yugoslavia, which is very important for manufacturing fixators and implants used in Serbia and beyond . It is of great importance that the production and processing of these materials is accurate and clean, in order to reduce potential human disorders (e.g. poisoning) to a minimum.